Cu(II) AND Zn(II) COMPLEX COMPOUNDS WITH BIGUANIDES AROMATIC DERIVATIVES. SYNTHESIS, CHARACTERIZATION, BIOLOGICAL ACTIVITY - Ticuţa Negreanu-Pîrjol; Bogdan Negreanu-Pîrjol; Mirela Călinescu; Florina Dumitru; Rodica Sîrbu; Ramona Stoicescu; Ghassoub Rima; Cornelia Guran (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In this paper we report the synthesis, physical-chemical characterization and antimicrobial activity of some new complex compounds of hetero-aromatic biguanides ligands, chlorhexidine base (CHX) and chlorhexidine diacetate (CHXac2) with metallic ions Cu(II) and Zn(II), in different molar ratio. The synthesized complexes were characterized by elemental chemical analysis and differential thermal analysis. The stereochemistry of the metallic ions was determined by infrared spectra, UV-Vis, EPR spectroscopy and magnetic susceptibility in the aim to establish the complexes structures. The biological activity of the new complex compounds was identified in solid technique by measuring minimum inhibition diameter of bacterial and fungal culture, against three standard pathogen strains, Escherichia coli ATCC 25922, Staphilococcus aureus ATCC 25923 and Candida albicans ATCC 10231. The results show an increased specific antimicrobial activity for the complexes chlorhexidine:Cu(II) 1:1 and 1:2 compared with the one of the Zn(II) complexes.